Ecomorphological variation in Sceloporus vandenburgianus (Squamata: Phrynosomatidae) across the sky-islands Southern California and Northern Baja California - Gregory, Jeren J.; Murdoch, Matthew; Chau, Elizabeth; Grismer, L. Lee; Grismer, Jesse L. (Zootaxa, 2025)
The mountain ranges of Southern California and Northern Baja California are unique upland ecosystems composed of a series of isolated sky-islands. The habitat composition among these montane isolates varies from more woodland with a closed canopy to more rocky habitats with large granite boulders with an open canopy. Sceloporus vandenburgianus is a montane habitat generalist that ranges across all the sky-islands of Southern California and Northern Baja California and has different refugia preferences at varying localities. In this study, we developed a morphometric dataset to test the hypothesis that there are ecomorphological differences among the sky-island populations of S. vandenburgianus that correspond to refugia preferences across these sky-islands. Our data support the hypothesis of local adaptation to different habitat and demonstrate that there are statistically significant differences in head shape between populations that live in rocky habitats versus mountain tops with more forested woodland canopies.